2007
DOI: 10.1007/s10867-007-9040-5
|View full text |Cite
|
Sign up to set email alerts
|

The Rate- and Species-Dependence of Short-Term Memory in Cardiac Myocytes

Abstract: Short-term memory is an intrinsic property of paced cardiac myocytes that reflects the influence of pacing history, and not just the immediately preceding diastolic interval (DI), on the action potential duration (APD). Although it is recognized that shortterm memory affects the dynamics of cardiac myocytes in general, and the onset of irregular cardiac rhythm in particular, its has never been adequately quantified or measured directly in experiments or numerical simulations, mainly due to the absence of appro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 24 publications
0
13
0
Order By: Relevance
“…Cardiac memory is an established property of paced cardiac myocytes to reflect the influence of pacing history and adapt and respond to novel stimuli. Several experimental studies and numerical simulations have shown that memory plays a role in modulating cardiac dynamics [ 30 , 31 ]. Indeed, in future studies, we will examine post-VNS recovery after a longer time delay.…”
Section: Discussionmentioning
confidence: 99%
“…Cardiac memory is an established property of paced cardiac myocytes to reflect the influence of pacing history and adapt and respond to novel stimuli. Several experimental studies and numerical simulations have shown that memory plays a role in modulating cardiac dynamics [ 30 , 31 ]. Indeed, in future studies, we will examine post-VNS recovery after a longer time delay.…”
Section: Discussionmentioning
confidence: 99%
“…Our short-term results indicated that on average cardiovascular variables recover to pre-VNS level almost 60 min after VNS is terminated. One possible explanation for this delayed effect could be contribution of VNS to the phenomenon called cardiac memory in which cardiomyocytes dynamics can be adapted based on the pacing history and response to stimuli (Tolkacheva, 2007).…”
Section: Long-term Cardiovascular Effectsmentioning
confidence: 99%
“…3. There are other approaches that quantify the amount of cardiac memory, one of which is via a restitution portrait pacing protocol (8,23). Although current restitution portrait protocols are relevant only to deterministic pacing by requiring that the APD and DI values reach a constant steady state and that their steady-state sum equals the BCL, their adaptation and use in the context of stochastic pacing and memory should be investigated in future work.…”
Section: Study Limitationsmentioning
confidence: 99%
“…The concept of short-term cardiac memory reflects the fact that a specific APD at a specific myocyte depends on the history of its electrical activity and therefore can be described as a function of its preceding activation properties, such as previous APDs, previous diastolic intervals (DIs), or previous intracellular ion concentrations. The ionic mechanisms underlying shortterm cardiac memory are not yet fully understood (8), despite some evidence in the literature pointing out the involvement of the intracellular concentration of sodium, [Na þ ] i . Both Schaeffer et al (9) and Decker et al (10) found that by holding [Na þ ] i constant, most of the cardiac memory features were eliminated.…”
Section: Introductionmentioning
confidence: 99%